A new Finnish flavor of feline coat coloration, "salmiak," is associated with a 95-kb deletion downstream of the KIT gene - Anderson, Heidi (Wiley-Blackwell, 2025)
Cats with a distinctive white hair pattern of unknown molecular cause have been discovered in the Finnish domestic cat population. Based on the unique appearance of these cats, we have named this phenotype salmiak ("salty licorice"). The use of a commercially available panel test to genotype four salmiak-colored cats revealed the absence of all known variants associated with white-haired phenotypic loci: full White (W), Spotting (Ws) and the Birman white Gloves associated (wg) allele of the KIT proto-oncogene (KIT) gene. Whole-genome sequencing on two salmiak-colored cats was conducted to search for candidate causal variants in the KIT gene. Despite a lack of coding variants, visual inspection of the short read alignments revealed a large ~95 kb deletion located ~65 kb downstream of the KIT gene in the salmiak cats. Additional PCR genotyping of 180 domestic cats and three salmiak-colored cats confirmed the homozygous derived variant genotype fully concordant with the salmiak phenotype. We suggest the newly identified variant be designated as wsal for "w salmiak".